Kinetics, thermodynamic and equilibrium study of Cr(VI) adsorption from aqueous solutions by NCL coal dust - Singh R.S.; Mondal M.K. (My University, 2025)
The waste material NCL coal dust was used as adsorbent for removal of Cr(VI) from aqueous solutions under batch adsorption experiments. The maximum removal of 99. 97% was recorded at pH 2. The time required to attain equilibrium was found to be 60 min. Adsorption kinetics was described by the Lagergren equation. The value of the rate constant of adsorption was found to be 0. 0615 min-1 at 16 mg dm-3 initial concentration and 298 K. The applicability of the Langmuir and Freundlich equations for the present system was also tested at different temperatures: 298, 313, and 328 K. Both thermodynamic parameters and temperature dependence indicated the endothermic nature of Cr(VI) adsorption on coal dust. The results showed that NCL coal dust is a promising adsorbent for the removal of Cr(VI) from aqueous solutions. © 2012 Korean Institute of Chemical Engineers, Seoul, Korea.